Biointeraction of Erythrocyte Ghost Membranes with Gold Nanoparticles Fluorescents - Garcia Casillas, Perla Elvia (2021)
The application of new technologies for treatments against different diseases is increasingly innovative and effective. In the case of nanomedicine, the combination of nanoparticles with biological membranes consists of a “camouflage” technique, which improves biological interaction and minimizes the secondary effects caused by these remedies. In this work, gold nanoparticles synthesized by chemical reduction (Turkevich 13 nm) were conjugated with fluorescein isothiocyanate to amplify their optical properties. Fluorescent nanoparticles were deposited onto the surface of hemoglobin-free erythrocytes. Ghost erythrocytes were obtained from red blood cells by density gradient separation in a hypotonic medium and characterized with fluorescence, optical, and electron microscopy; the average size of erythrocyte ghosts was 9 m. Results show that the functional groups of sodium citrate (COO-) and fluorophore (-N=C=S) adhere by electrostatic attraction to the surface of the hemoglobin-free erythrocyte membrane, forming the membrane–particle–fluorophore. These interactions can contribute to imaging applications, by increasing the sensitivity of measurement caused by surface plasmon resonance and fluorescence, in the context of biological membranes.